Cellulose Hydrogel with Hyaluronic Acid and Silver Nanoparticles: Sustained-Release Formulation with Antibacterial Properties against Pseudomonas aeruginosa - Mirian Sumini; Clara Ruiz de Souza; Gabriel Jonathan Sousa Andrade; Igor Roberto Cabral Oliveira; Sara Scandorieiro; Cesar Augusto Tischer; Renata Katsuko Takayama Kobayashi; Gerson Nakazato (MDPI AG, 2023)
Pathogenic bacteria resistant to conventional antibiotics represent a global challenge and justify the need for new antimicrobials capable of combating bacterial multidrug resistance. This study describes the development of a topical hydrogel in a formulation composed of cellulose, hyaluronic acid (HA), and silver nanoparticles (AgNPs) against strains of Pseudomonas aeruginosa. AgNPs as an antimicrobial agent were synthesized by a new method based on green chemistry, using arginine as a reducing agent and potassium hydroxide as a carrier. Scanning electron microscopy showed the formation of a composite between cellulose and HA in a three-dimensional network of cellulose fibrils, with thickening of the fibrils and filling of spaces by HA with the presence of pores. Ultraviolet-visible spectroscopy (UV-vis) and particle size distribution for dynamic light scattering (DLS) confirmed the formation of AgNPs with peak absorption at ~430 nm and 57.88 nm. AgNPs dispersion showed a minimum inhibitory concentration (MIC) of 1.5 µg/mL. The time-kill assay showed that after 3 h of exposure to the hydrogel containing AgNPs, there were no viable cells, corresponding to a bactericidal efficacy of 99.999% in the 95% confidence level. We obtained a hydrogel that is easy to apply, with sustained release and bactericidal properties against strains of Pseudomonas aeruginosa at low concentrations of the agent.